Tourism opportunities in rural areas - Varga-Nagy, Adrienn (Studia Mundi – Economica, 2016)
Nowadays, not only in Hungary, tourism as well as developments based on domestic tourism get more attention in both spatial and economic development strategies. Accordingly, I intended to highlight the importance of this sector. I examined the development of rural space through analyzing the tourism sector, since I believe that due to the harmony in our natural, economic and human resource, we have great potentials in this regard. Based on the abovementioned, I think that tourism may become a leading or supplementary sector of an area, providing a future perspective for the local population directly or indirectly. Despite of the fact that the country has favourable touristic conditions in general, I think that some of the areas do not have the necessary economic, infrastructural and human resources. As a principle, I believe that it is important to examine the priorities of economic development strategies of all regions, with special focus on tourism potentials. In order to discover the development potentials of the regions, we should analyze the internal conditions of their environment, the success factors, the influence of external factors as well as their potential use.